Multiscale characterization of cortical bone composition, microstructure, and nanomechanical properties in experimentally induced osteoporosis - Shah, Furqan A; Stoica, Adrian; Cardemil, Carina; Palmquist, Anders (Journal of biomedical materials research. Part A, 2018)
Cortical bone plays a vital role in determining overall bone strength. We investigate the structural, compositional, and nanomechanical properties of cortical bone following ovariectomy (OVX) of 12-week-old Sprague Dawley rats, since this animal model is frequently employed to evaluate the performance of implantable biomaterials in compromised bone healing conditions. Morphological parameters and material properties of bone in the geometrical center of the femoral cortex were investigated four and eight weeks post-OVX and in unoperated controls (Ctrl), using X-ray micro-computed tomography, backscattered electron scanning electron microscopy, Raman spectroscopy, and nanoindentation. The OVX animals showed increase in body weight, diminished bone mineral density, increased intracortical porosity, but increased bone mass through periosteal apposition (e.g., increases in periosteal perimeter, cortical cross-sectional thickness, and cross-sectional area). However, osteocyte densities, osteocyte lacunar dimensions, and the nanomechanical behavior on the single mineralized collagen fibril level remained unaffected. Our correlative multiscale investigation provides structural, chemical, and nanomechanical evidence substantiating earlier reports suggesting that rats ovariectomized at 12 weeks undergo simultaneous bone loss and growth, resulting in the effects of OVX being less obvious. Periosteal apposition contradicts the conventional view of bone loss in osteoporosis but appears advantageous for the greater functional demand imposed on the skeleton by increased body weight and fragility induced by increased intracortical porosity. Through a variety of morphological changes, it is likely that 12-week-old rats are able to adapt to OVX-related microstructural and compositional alterations. © 2017 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 997-1007, 2018.
Keywords: lineární modely; bone; Nanoparticles; Extracellular Matrix; osteoporóza; poréznost; Female; Osteocytes; počet buněk; ovariectomy; extracelulární matrix; zvířata; osteocyty; osteoporosis; femur; Minerals; Femur; kortikální kost; ženské pohlaví; potkani Sprague-Dawley; rentgenová mikrotomografie; Raman spectroscopy; Linear Models; Cortical Bone; nanočástice; X-Ray Microtomography; Porosity; Rats, Sprague-Dawley; Body Weight; Animals; Osteoporosis; biomechanika; tělesná hmotnost; Biomechanical Phenomena; minerály; Cell Count; nanoindentation